Perioperative Safety and Early Patient and Device Outcomes Among Subcutaneous Versus Transvenous Implantable Cardioverter Defibrillator Implantations : A Randomized, Multicenter Trial - Healey, Jeff S; Krahn, Andrew D; Bashir, Jamil; Amit, Guy; Philippon, François; McIntyre, William F; Tsang, Bernice; Joza, Jacqueline; Exner, Derek V; Birnie, David H; Sadek, Mouhannad; Leong, Darryl P; et al. (Annals of internal medicine, 2022)
Implantable cardioverter defibrillators (ICDs) improve survival in patients at risk for cardiac arrest, but are associated with intravascular lead-related complications. The subcutaneous ICD (S-ICD), with no intravascular components, was developed to minimize lead-related complications. To assess key ICD performance measures related to delivery of ICD therapy, including inappropriate ICD shocks (delivered in absence of life-threatening arrhythmia) and failed ICD shocks (which did not terminate ventricular arrhythmia). Randomized, multicenter trial. (ClinicalTrials.gov: NCT02881255). The ATLAS trial. 544 eligible patients (141 female) with a primary or secondary prevention indication for an ICD who were younger than age 60 years, had a cardiogenetic phenotype, or had prespecified risk factors for lead complications were electrocardiographically screened and 503 randomly assigned to S-ICD (251 patients) or transvenous ICD (TV-ICD) (252 patients). Mean follow-up was 2.5 years (SD, 1.1). Mean age was 49.0 years (SD, 11.5). The primary outcome was perioperative major lead-related complications. There was a statistically significant reduction in perioperative, lead-related complications, which occurred in 1 patient (0.4%) with an S-ICD and in 12 patients (4.8%) with TV-ICD (-4.4%; 95% CI, -6.9 to -1.9; = 0.001). There was a trend for more inappropriate shocks with the S-ICD (hazard ratio [HR], 2.37; 95% CI, 0.98 to 5.77), but no increase in failed appropriate ICD shocks (HR, 0.61 (0.15 to 2.57). Patients in the S-ICD group had more ICD site pain, measured on a 10-point numeric rating scale, on the day of implant (4.2 ± 2.8 vs. 2.9 ± 2.2; < 0.001) and 1 month later (1.3 ± 1.8 vs. 0.9 ± 1.5; = 0.035). At present, the ATLAS trial is underpowered to detect differences in clinical shock outcomes; however, extended follow-up is ongoing. The S-ICD reduces perioperative, lead-related complications without significantly compromising the effectiveness of ICD shocks, but with more early postoperative pain and a trend for more inappropriate shocks. Boston Scientific.